IMF Staff papers : Volume 35 No. 4. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1988)
An intertemporal optimizing model of a small open economy is used to analyze how terms of trade changes affect real exchange rates and the trade balance. Temporary current, (expected) future, and permanent changes in the terms of trade are considered. The results suggest that the relationship between the terms of trade and the current account (the so-called Harberger-Laursen-Metzler effect) is sensitive to whether the model incorporates nontradable goods. Thus, the real exchange rate may be an important variable through which terms of trade shocks are transmitted to the current account.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet